A perfect time for pandas - Osborne, Mary Pope (Osborne, Mary Pope. Magic tree house series, 2012)
Time-traveling brother-and-sister team Jack and Annie have to find a certain kind of food--the fourth thing needed to save Merlin's beloved penguin, Penny. The magic tree house whisks them off to a village in the mountains of southeast China, close to a world-famous panda reserve. Will it be their easiest adventure yet? Not a chance! Jack and Annie don't know it, but they've arrived on the day of a historic earthquake! How will Jack and Annie survive when the giant quake strikes? Will they be able to rescue the pandas? And how will they ever get back to the tree house so that they can fulfill their quest to save Penny as well?